Radiographic Response of Solitary Plasmacytomas After Conformal Radiotherapy May Be Delayed: Outcomes in the 3D Era. (24th November 2022) - Kosydar, Samuel; Gulhane, Avanti; Libby, Edward; Cowan, Andrew J.; Kwok, Mary; Lee, Sarah S.; Green, Damian J.; Coffey, David; Holmberg, Leona A.; Chen, Delphine L.; Tseng, Yolanda D.
Abstract : Objective: Although recurrence rates after radiotherapy for solitary plasmacytoma (SP) are well established, little is known about how SP responds radiographically, as most historical patients were treated in the 2D era. We evaluated the response to radiotherapy among SP patients staged and treated with 3D techniques, including proton therapy, which has not yet been previously reported. Methods and Materials: Between 2007 and 2021, 15 SP patients (4 extramedullary, 11 bone) staged with 3D imaging and bone marrow evaluation were consecutively treated with definitive radiotherapy. The best response was categorized in 9 evaluable patients according to response evaluation criteria in solid tumors (RECIST) and positron emission tomography response criteria in solid tumors (PERCIST). Results: With a median follow-up of 34 months, 4 patients relapsed. The median time to the best response was ~2 years (26.6 mo RECIST, 25.4 mo PERCIST). Response rates differed based on response assessment criteria. PERCIST was associated with higher rates of complete (85.7%) or partial response (14.3%) compared with RECIST (16.7% complete, 33.3% partial). Two-year and 4-year PFS for extramedullary SP were 100% and 75%, compared with 91% and 55% for bone ( P =0.75). Patients treated with proton therapy (n=5) did not appear to have different patterns of relapse (1 marginal, 1 distant) compared with those treated with photons or electrons (n=10; 2 distant). Conclusions: More conformal dose distribution with proton therapy does not appear to alter patterns of recurrence. Although response rates differ based on criteria by both RECIST and PERCIST assessments, the radiographic response may be slow and requires validation in other cohorts.